Характер особливостей розв'язку узагальненої крайової задачі для квазілінійної параболічної системи - Лопушанська, Г.П.; Чмир, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
For some subspaces of the weight L1-space, the existence of a solution of the normal boundary-value problem for a quasilinear parabolic system with generalized functions from the space (C∞)´ given on the boundary of a domain is proved. The character of singularities of the solution (point-like and on the whole boundary of the domain) is determined.